Computation of Neutron Coefficients for B2O3 reinforced Composite - ORUNCAK, Bekir (International Journal of Computational and Experimental Science and Engineering, 2023)
Radiation is an important phenome and has been used in many different fields since its discovery. Although there are different types of radiation, neutron is one of the most interesting types as it is an uncharged particle. This character made neutron is more dangerous radiation types than others and thus protection from neutron effect requires more care. In this paper neutron attenuation coefficients of B2O3 reinforced composite have been investigated using Phy-X/PSD software.